The Influence of Product Quality, Price Fairness, Brand Image, and Customer Value on Purchase Decision of Toyota Agya Consumers: A Study of Low Cost Green Car - Freddy Pandapotan Simbolon; Elvira Rossi Handayani; Menik Nugraedy (Bina Nusantara University, 2020)
The research aimed to investigate the influence of product quality, price fairness, brand image, and customervalue on purchase decision in the Low Cost Green Car (LCGC). The research applied a quantitative methodwith survey design. It was conducted in Auto2000 Jakarta with a sample of 100 Toyota Agya owners using anaccidental sampling technique. Data analysis for hypothesis test used path analysis calculated with SPSS software.The research findings indicate that product quality, brand image, and customer value significantly influence thepurchase decision of Toyota Agya consumers. Meanwhile, price fairness has no effect on the purchase decision.The results also show that product quality, price fairness, and brand image affect customer value. Based on thesefindings, in developing LCGC, manufacturers must pay attention to product quality, build brand reputation, andcreate more value for consumers.